Experiences on the use of an automatic C++ solution grader system - Sioson, Allan A. (2013 Fourth International Conference on Information, Intelligence, Systems and Applications (IISA), 2013)
The codeCurator is an automatic C++ solution grader used in teaching programming to first year College students in Ateneo de Naga University. It provides programming exercises and challenge problems based on a prescribed sequence of programming topics. The exercises and challenge problems are designed to help students get a grip on formulation of functions, class methods, complete class implementation, or complete stand-alone programs in C++. Solutions are typically short and are checked using automatic testing techniques similar to online judge of ACM ICPC problems. In this paper, we present an analysis of the frequency of submissions, similarity of submitted solutions, categories of problems, and prospects on how to achieve an effective delivery of instruction.